The effectiveness of the cylinder block on stilling basin as energy dissipation system - Nor Farahiah, Ibrahim (2015)
Flow discharge from a spillway to is due to the force of gravity. Therefore, the steeper the outlet spillway, the magnitude of flow velocity will higher. Consequently of high velocity is able to cause erosion and will damage spillway itself. To overcome these problems, the velocity must be reduced. To achieve the purpose, the used of velocity reducing structures are recommended. Many researches have been conducted to identify the effectiveness and economical of velocity reducing structures. Velocity reducing structures is one of the hydraulics structures that reduce high velocity water flow especially at downstream of the spillways. The objective of this study is to determine the performance and effectiveness of velocity reducing structures on the stilling basin through laboratory test. In this study, tests are conducted on cylindrical shape blocks of the velocity reducing structures on the stilling basin. The blocks used in this study have different size and surface roughness, different slope of spillway and different flow rate. The spillway model was erected at the workshop. During the test, the flow depth and velocity are observed before and after the blocks locating on the stilling basin. For concrete blocks size 50×100mm with slope 27˚, the best pattern with a highest percentage reduction in velocity is pattern 3 with 47.03% and for slope 15˚ the percentage reduction in velocity is 50.12%. Based on the results, its shows that the lower slope can increase the percentage of reduction in velocity